Realization of The Politeness Strategies of Directive Utterances by The Students of English Department at The Fourth Semester at Muhammadiyah University of Surakarta - Purnomo, Arif Indra, Dra. Siti Zuhriah Ariatmi, M.Hum (2016)
This descriptive qualitative research aims at describing (1) syntactical form of directive utterances, (2) the realization of politeness strategy (3) the relationship of directive utterance with politeness strategies. The data used in this research are utterances which are used by the students. The technique of collecting data used DCT model. The techniques of analyzing data are data reduction, analysis, and conclusion. The data are analyzed by using politeness theory (Brown and Levinson, 1987), grouping the sentences uses theory from (Frank, 1972) and politeness degree uses theory from (Leech, 1999). The result indicated that: there are 4 types' linguistic forms at directive utterances. (1) In request strategy the researcher found 3 linguistic forms namely: interrogative sentence takes 64%, imperative sentence takes 19%, and declarative sentence takes 17%. In order strategy the researcher found 4 linguistic forms namely: interrogative sentence takes 48%, imperative sentence takes 37%, and declarative sentence takes 13% and exclamatory sentence 2% (2) there are five politeness strategies. In request strategy the researcher found 4 politeness strategies namely: bald on record 18%, positive politeness 17%, negative politeness 62%, and off record 2%. In order strategy the researcher found 3 linguistic forms namely: bald on record 28%, positive politeness 12%, and negative politeness 59%. (3) The relationship of syntactical form directive utterance with politeness strategy, interrogative sentence have relationship with negative politeness, imperative sentence have relationship with positive politeness and bald on record, declarative sentence have relationship with off record, and exclamatory sentence have relationship with do not do FT. Keywords: directive utterance, descriptive qualitative, politeness theory.